Evaluation of serum procalcitonin level as a biomarker for disease severity in COVID-19 patients. (September 2021) - Waris, A.; Din, M.; Iqbal, N.; Yar, L.; Khalid, A.; Nawaz, M.; Baset, A.; Ali, M.
Abstract: The pandemic of coronavirus disease 2019 (COVID-19) has infected millions of individuals around the globe. Forecasting the COVID-19 severity is essential, and various biomarkers could be used to evaluate it. The current study was therefore aimed to evaluate the serum pro-calcitonin (PCT) level as a biomarker for bacterial co-infection and disease severity in COVID-19 patients. A total of 430 COVID-19 positive individuals were examined, in which 332 (77.2%) were male individuals while 98 (22.8%) were female individuals. Among the examined samples, 281 were classified as moderate (PCT value 0.07 ± 0.06 ng/mL), 95 were severe (PCT value 0.5 ± 0.4 ng/mL), and 54 were classified as critical (PCT value > 1 ng/mL) individuals. The increase in the total serum level of PCT was observed with the severity of the disease (p < 0.05). The statistical analysis represented no association of PCT value with gender (p 0.9650) while revealed a significant association (p < 0.001) with the age and PCT value in COVID-19 patients. It can be concluded that the serial PCT measurement could determine the prognosis of the disease and the presence of bacterial co-infection in COVID-19 patients. Further exploration of the topic is needed to evaluate the effect of different therapies on the PCT level and to prescribe specific treatment options for coinfection.